The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/sj.bdj.2014.48
|View full text |Cite
|
Sign up to set email alerts
|

Minimal intervention dentistry II: part 1. Contribution of the operating microscope to dentistry

Abstract: The different aspects of treatment of periodontal disease and mucogingival defects all require an accurate diagnosis in addition to good control and precision during therapeutic procedures. Magnification aids and microsurgery, combined with minimally invasive techniques, can best meet these requirements. The suitability of treatment, the healing time, pain levels and postoperative scarring are all improved and the patient benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
7
0
2
Order By: Relevance
“…The findings of a 2-visit study (Hashem et al 2015) that used Carisolv gel for excavation of carious dentin without magnification showed that only 65.4% of teeth were deemed healthy using CBCT at M12. This finding is similar to the current control group (73.3%) but lower than the success rate in the experimental group (90%) in which operative microscopy was used, suggesting that the use of the operating microscope, increasing the visual capacity of the operator, may contribute to avoiding unnecessary tissue damage (Sitbon et al 2014). Therefore, at this stage of intervention, there remains scope for the operator to optimize a tissue environment conducive to pulp repair and healing.…”
Section: Discussionsupporting
confidence: 76%
“…The findings of a 2-visit study (Hashem et al 2015) that used Carisolv gel for excavation of carious dentin without magnification showed that only 65.4% of teeth were deemed healthy using CBCT at M12. This finding is similar to the current control group (73.3%) but lower than the success rate in the experimental group (90%) in which operative microscopy was used, suggesting that the use of the operating microscope, increasing the visual capacity of the operator, may contribute to avoiding unnecessary tissue damage (Sitbon et al 2014). Therefore, at this stage of intervention, there remains scope for the operator to optimize a tissue environment conducive to pulp repair and healing.…”
Section: Discussionsupporting
confidence: 76%
“…Generally, the microscope is significantly more expensive than the loupe due to various optic designs that provide substantially higher levels of magnification without causing eye strain. [ 21 65 ] The heavy optics is, in turn, justifiably supported by hinges and arms that stay static in any position.…”
Section: Drawbacks Of Magnification Devicesmentioning
confidence: 99%
“…In dentistry, these values can be compromised even further by the low luminosity in the buccal cavity. 50 Devices of clinic microscopes and head-mounted loop, which equipped dentists with accurate views, are thus considered as visual basis. 51…”
Section: Consensus Statementmentioning
confidence: 99%
“…55–57 Comparatively, DOMs are more advanced in: (1) alternative scales with high-level magnifications; (2) better ergonomic posture; (3) coaxial illumination device equipped; (4) video recording system with high-performance cost ratio. 50,58,59…”
Section: Consensus Statementmentioning
confidence: 99%